Rethinking, Re-storying, and Reclaiming Narratives of Aging in Music Education Research - Laes, Tuulikki (Southern Illinois University, 2023)
In this article, I address the contemporary discussion of later-life courses in music education research and how it might perpetuate the discrimination and stereotyping of older adults. Drawing from the sociology of aging, I aim to show that one possible way to tackle the ageist assumptions in music education is to reflect on rethinking, re-storying, and reclaiming the master narratives of aging by replacing the dominant linear life span view with an intersectional life course approach. Furthermore, I will present ideas to connect qualitative narrative inquiry with systems thinking, to challenge the practices and research traditions that contribute to the sustainment of stereotypical mental models of aging in music education and move towards a framework of sustainable aging. Finally, the transformative potential of such inquiry will benefit not only music educators interested in later-life questions but also the field at large. The music education of young children, for instance, can be seen as an investment in the musical agency of future older people.
Keywords: musiikkikasvatus; musiikki; ikääntyminen; ikääntyneet; elinikäinen oppiminen; oppiminen